Pengembangan Sistem Informasi Pemesanan Jasa Laundry Berbasis Web pada One Laundry Menggunakan Model Waterfall - Muhamad Fajar (SENTRI: Jurnal Riset Ilmiah, 2025)
This research aims to develop a web-based information system for ordering laundry services at One Laundry. Currently, order recording, transaction processing, and report preparation are still carried out manually, so data are often duplicated, lost, or difficult to trace when customers ask about the status of their laundry. These conditions reduce service quality and make it difficult for the owner to monitor business performance. The proposed system is designed to digitalize the order flow starting from customer registration, order input, calculation of service costs, payment recording, until printing transaction reports. The system was developed using the waterfall model, with stages of requirements analysis, system design, implementation, and testing. Data were collected through observation, interviews with the owner and employees, documentation of existing forms, and literature study on similar systems. The application was built using PHP and MySQL with a responsive web interface so it can be accessed via desktop or mobile browser. System testing used black-box testing on each main function and limited user acceptance testing for One Laundry’s owner and staff. The developed system provides features for managing customer data, service packages, orders, order status, payments, and reports. Testing results show that the system can run according to functional requirements and makes it easier for the owner to manage transaction data and monitor daily income. Therefore, the web-based laundry ordering information system can be used as a solution to improve the efficiency and accuracy of service at One Laundry.